Teaching Folk Life and National Traditions in Visual Arts Lessons through Interactive Pedagogical Methods - Usmonova Ruxshona Feruz qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article examines the use of interactive pedagogical methods to teach schoolchildren about folk life and national traditions in visual arts lessons. The study emphasizes strategies that enhance students’ engagement, creativity, and understanding of cultural heritage. By integrating interactive activities, such as group projects, role-playing, discussions, and collaborative artwork, teachers can facilitate a deeper comprehension of traditional customs, festivals, and national motifs. Practical recommendations are provided for designing lessons that develop students’ artistic skills, aesthetic perception, and cultural awareness through active participation.